2013
DOI: 10.1016/j.gdata.2013.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Computational identification of microRNAs and their targets in Catharanthus roseus expressed sequence tags

Abstract: No study has been performed on identifying microRNAs (miRNAs) and their targets in the medicinal plant, Catharanthus roseus. In the present study, using the comparative genomics approach, we have predicted two potential C. roseus miRNAs. Furthermore, twelve potential mRNA targets were identified in C. roseus genome based on the characteristics that miRNAs exhibit perfect or nearly perfect complementarity with their targeted mRNA sequences. Among them many of the targets were predicted to encode enzymes that re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 38 publications
2
36
0
Order By: Relevance
“…The regulation of miR5021 in terpenoid backbone biosynthesis was reported earlier in Catharantus roseus by modulating the expression of geranylgeranyl-di-phosphate (Pani and Mahapatra, 2013). Our result suggests the possible role of the miR5021, miR414 and miR156 in the regulation of essential oil biosynthesis.…”
Section: Functional Annotation and Pathway Analysissupporting
confidence: 82%
“…The regulation of miR5021 in terpenoid backbone biosynthesis was reported earlier in Catharantus roseus by modulating the expression of geranylgeranyl-di-phosphate (Pani and Mahapatra, 2013). Our result suggests the possible role of the miR5021, miR414 and miR156 in the regulation of essential oil biosynthesis.…”
Section: Functional Annotation and Pathway Analysissupporting
confidence: 82%
“…Though various genome-wide experimental studies have reported candidate TFs hitherto (Hu et al 2014;Wang et al 2010;Zhu et al 2012), not much systems-level work has been done to assimilate the data. With increase in high-throughput proteomic/genomic studies and computational facilities, identification and annotation of TFs at genome scale are now being used to understand the regulation of biological mechanism (He et al 2010;Pani and Mahapatra 2013). Although TFs are initially identified by computational approaches, they have also been validated by experimental approaches (Van Dijk et al 2010) presenting the strength of computational protocols.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their broad pharmacological properties, limited information is available about regulatory factors involved in the synthesis of secondary metabolites (Chou and Kutchan 1998;Wink 2010) which further affect the yield and spectrum of such pharmacologically important compounds (De Luca and St Pierre 2000;Vom Endt et al 2002). Catharanthus roseus has been considered as model plant to understand TIA pathway (Facchini and De Luca 2008;Pani and Mahapatra 2013), and TF families such as WRKY (Suttipanta et al 2011;Schluttenhofer et al 2014) and AP2EREBP have been reported to regulate metabolite synthesis (van der Fits and Memelink 2000;Li et al 2013). Also, bHLH and MYB-like TFs are reported to be highly expressed under jasmonate response but needs to be confirmed for their regulatory role in TIA pathway (Memelink and Gantet 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The miR5021 participate in multiple biological and metabolic processes, including signal transduction, stress response, MYB transcription factors and plant development in Brassica oleracea (Wang et al, 2012a) and cotton (Wang et al, 2012b). It plays important role in plant development in amino acid (cysteine and methionine) metabolism in Ocimum basilicum (Singh and Sharma, 2014) and regulates ethylene and polyamines syntheses in Catharanthus roseus (Pani and Mahapatra, 2013). Being one of the largest miRNAs families in response to cold stress, it may regulate cellular, physiological or developmental processes specific to peach and/or other tree species (Barakat et al, 2012).…”
Section: Target Prediction Of Mirnas and Functional Analysismentioning
confidence: 99%